2019
DOI: 10.3390/ijerph16101807
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Infection and Vaccination: Knowledge, Beliefs, and Behaviors among Parents in Italy

Abstract: This study was designed to investigate the knowledge, beliefs, and behaviors about rotavirus infection and its vaccination in a sample of parents in Naples, Italy. The survey was conducted between June and December 2018 among parents of children aged 3 months to 3 years. A total of 40.7% of the study subjects declared that they had heard about rotavirus infection and 60.8% and 59.2% were aware about the vaccination and of its availability in Italy. Parents with a child aged <1 year and those who reported th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
1
20
0
4
Order By: Relevance
“…The findings from this survey are consistent with several previous results from similar studies among different groups of individuals that have demonstrated the importance of scientific information for their knowledge and attitudes. Indeed, as described in prior studies [5,17,[25][26][27][28][29], it is evident from the multivariate analysis that receiving information from scientific journals and educational activities facilitates the emergence of pharmacists who have better knowledge and have more positive attitudes. This is important because the pharmacists themselves, in order to effectively influence others, must be well equipped with an appropriate level of knowledge, and interventions should be aimed at including such sources as an important conduit of travel medicine-related information, which can support the pharmacists' confidence.…”
Section: Discussionmentioning
confidence: 85%
“…The findings from this survey are consistent with several previous results from similar studies among different groups of individuals that have demonstrated the importance of scientific information for their knowledge and attitudes. Indeed, as described in prior studies [5,17,[25][26][27][28][29], it is evident from the multivariate analysis that receiving information from scientific journals and educational activities facilitates the emergence of pharmacists who have better knowledge and have more positive attitudes. This is important because the pharmacists themselves, in order to effectively influence others, must be well equipped with an appropriate level of knowledge, and interventions should be aimed at including such sources as an important conduit of travel medicine-related information, which can support the pharmacists' confidence.…”
Section: Discussionmentioning
confidence: 85%
“…Nonetheless, the findings of the present study also determined that fewer respondents reported hearing about the vaccine from scientific journals. Moreover, it is well known that health-care workers, mainly physicians involved in primary and preventive care, should intensively promote vaccination because their recommendation and information dissemination to patients has a significant impact on vaccination rates [ 30 , 31 , 32 , 33 ]. Therefore, health organizations and health-care workers are required to provide, especially in the event of a new disease such as COVID-19 that is globally at the center of attention, communication regarding immunization by coupling their recommendation with clear messages regarding vaccine safety, effectiveness, and benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of having heard about rotavirus diarrheal disease and rotavirus vaccine influenced knowledge since information related to vaccine availability and its benefits gained from experience will increase public knowledge about rotavirus infection and vaccination. This information can be obtained from communication with health workers and education in all opportunities related to vaccination [19]. Information exposure to respondents who had been vaccinated should higher compared to those who have never been vaccinated.…”
Section: Discussionmentioning
confidence: 99%